2017
DOI: 10.1590/1413-785220172504171249
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Postural Changes and Temporomandibular Disorders in Students

Abstract: Objective: The aim of this study was to identify the incidence of postural changes and temporomandibular disorders (TMD) in children and adolescents . Methods: We selected 117 individuals aged 10-18 years from a state school in the Zona da Mata region of Minas Gerais. The students were evaluated in four stages: assessment of body weight and height and calculation of body mass index; posture evaluation using a questionnaire developed by the researchers; application of a questionnaire recommended by the American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
0
16
0
3
Order By: Relevance
“…The severity of TMD is an important finding to evaluate the progression and impact of dysfunction in the life of the affected individuals 15,18 . However, to the best of our knowledge, the design of studies involving TMD and body posture generally only associates postural conditions with the presence of dysfunction [6][7][8]12 and it does not seek to investigate this relationship with TMD severity.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of TMD is an important finding to evaluate the progression and impact of dysfunction in the life of the affected individuals 15,18 . However, to the best of our knowledge, the design of studies involving TMD and body posture generally only associates postural conditions with the presence of dysfunction [6][7][8]12 and it does not seek to investigate this relationship with TMD severity.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the findings of this study, it has been reported that TMD is not frequently observed during primary dentition, while it is increasingly observed during mixed dentition (7). Chaves et al (34) reported that the alterations in head position were observed in 56% of cases of moderate to severe TMD in individuals in the 10-18 years age group. Cortese et al (35) stated that FHP was one of the most common postural anomalies at 10-15 years of age, and this was a risk factor for TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the mixed dentition period should be carefully assessed for the presence of TMD and postural irregularities, since TMJ related diseases are expected to increase especially after the primary dentition period. It has been reported that TMD stimulate the effects of masticatory muscles on the compensator mechanism and this biomechanical adaptation pulls the shoulders upwards (34). The occurrence of postural disorders is believed to be due to excessive stresses on the cervical muscles depending on the increased activity of the masticatory muscles to compensate for joint disease in TMD individuals (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She is involved in swallowing, chewing, breathing and speech. The opening movement and closing the mouth is accomplished by a set musculoskeletal joint-called stomatognathic system in which highlights the most complex joint in the human body, called a temporomandibular joint (TMJ) [4].…”
Section: Introductionmentioning
confidence: 99%